The Practical encyclopedia of good decorating and home improvement - Gipp, Jennifer (Australia : Thomson Course Technology, 2008)
This book introduces middle school learners to basic technology concepts and skills through hands-on computer activities.
Chapter 1. Introduction to spreadsheets -- Chapter 2. Function formulas -- Chapter 3. Charts -- Chapter 4. Additional features
Includes index.
Keywords: ELECTRONIC SPREADSHEETS